Evaluation of Mechanical and Biological Properties of Heat-Cured Denture Base Fabricated with Recycled PMMA Powder - Halib, Nadia; Said, Zulfahmi; Sa’adon , Muhamad Azfar Fathi; Mohd Sabri , Nur Aina Aqilah (International Journal of Dental Materials, 2025)
Background: Heat-cure polymethylmethacrylate (PMMA) is widely used in dentistry as a denture base material and for training students in fabricating acrylic-based dental appliances. These appliances are typically discarded after training, leading to significant acrylic waste. Aim: To recycle discarded denture base materials to produce recycled PMMA powder for use in denture base fabrication. Materials and Methods: The recycled PMMA (rPMMA) powder was produced by grinding the used denture base into the desired particle and later incorporated in different concentrations, 20% and 50%, into the commercial PMMA for denture base fabrication. The mechanical and biological properties of the PMMA modified with rPMMA were investigated. The unmodified denture base fabricated with 100% commercial PMMA powder served as a control group. Results: The incorporation of 50% rPMMA powder into the PMMA denture base showed slightly more flexural strength (125.80 ± 17.53 MPa) compared to the 20% modified and the control groups. No significant change in the hardness was observed among the groups. Less colony-forming units were observed in the 20% rPMMA modified group (186.33) compared to the other groups. Conclusion: Denture base materials modified with recycled PMMA (rPMMA) exhibited acceptable mechanical properties and a reduced colony-forming unit (CFU) count compared to unmodified materials.